2018
DOI: 10.1002/cam4.1449
|View full text |Cite
|
Sign up to set email alerts
|

A novel rapid quantitative method reveals stathmin‐1 as a promising marker for esophageal squamous cell carcinoma

Abstract: Stathmin‐1 is a microtubule depolymerization protein that regulates cell division, growth, migration, and invasion. Overexpression of stathmin‐1 has been observed to be associated with metastasis, poor prognosis, and chemoresistance in various human cancers. Our previous studies found that serum stathmin‐1 was significantly elevated in patients with esophageal squamous cell carcinoma (ESCC) by ELISAs. Here, we constructed high‐affinity monoclonal antibodies and then developed a competitive AlphaLISA for rapid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Until now, besides the established markers (TP53, p16, and Ki-67), several proteins were reported to be differentially expressed in STIC lesions including Stathmin 1 [19], signal transducer and activator of transcription 3 (phosphorylated STAT3 Tyr705) and suppression or loss of protein inhibitor of activated STAT3 (PIAS3) [20], Bcl-2 and γH2AX [21], Rsf-1 (HBXAP), cyclin E, and fatty acid synthase (FASN) [22], CD117 and ALDHA1 [23] and HMGA2 [24]. Of these proteins, differential circulating levels of Stathmin 1, FASN, ALDH1 were observed in esophageal, colorectal and lung cancers, and differential levels of Bcl-2 in OC, although none demonstrated high classification power [25][26][27][28][29]. With a better understanding in STIC development, new and better biomarkers for screening purposes can be envisioned.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, besides the established markers (TP53, p16, and Ki-67), several proteins were reported to be differentially expressed in STIC lesions including Stathmin 1 [19], signal transducer and activator of transcription 3 (phosphorylated STAT3 Tyr705) and suppression or loss of protein inhibitor of activated STAT3 (PIAS3) [20], Bcl-2 and γH2AX [21], Rsf-1 (HBXAP), cyclin E, and fatty acid synthase (FASN) [22], CD117 and ALDHA1 [23] and HMGA2 [24]. Of these proteins, differential circulating levels of Stathmin 1, FASN, ALDH1 were observed in esophageal, colorectal and lung cancers, and differential levels of Bcl-2 in OC, although none demonstrated high classification power [25][26][27][28][29]. With a better understanding in STIC development, new and better biomarkers for screening purposes can be envisioned.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding OP18, also termed oncoprotein 18 and stathmin-1, immunohistochemical analyses of human donors and studies in the bladder cancer cell line T24 indicated that over-expression of OP18 is related to malignant cell characteristics. It is noteworthy that the role of increased expression of OP18 for tumor development and metastatic growth seems to be true also for other tumor types including esophageal squamous cell carcinoma [20,21] and lung adenocarcinoma [22]. In summary, these studies warrant a closer look at OP18 transcripts as an RNA-based tumor marker in BCa.…”
Section: Introductionmentioning
confidence: 81%
“…Knockdown stathmin-1 expression enhanced the sensitivity of ESCC cell line to docetaxel and radiation[42]. Stathmin-1 can be delivered by exosomes and then promote the division, growth, migration, and invasion of esophageal squamous cells[43].…”
Section: Exosome and Esophageal Cancer Tumorigenesismentioning
confidence: 99%
“…Studies have confirmed that the number or contents (including RNA and proteins) of exosomes in the circulating blood are of use as a biomarker for cancers, such as lung cancer[46], prostate cancer[47], colorectal cancer[48], as well as EC[18,28,43,49].…”
Section: Exosomes As Biomarkers For Early Diagnosis and Prognostic Prmentioning
confidence: 99%
See 1 more Smart Citation